Hubungan Kepercayaan Diri dengan Interaksi Sosial pada Remaja Kecanduan Game Online di SMP Negeri 1 Asembagus - Rizki Maulana Hidayatullah; Ayu Eliza (LP2M Universitas Ibrahimy, 2024)
Confidence is one of the things social interaction well.But for the students had been addicted to online games of course would be questionable, people were addicted to online games would be hard to interact with others because they already feel comfortable with their activities.This study bertujuhan identify the effects confidence on social interaction in adolescents are addicted to online games in junior high schools the sample of 1 asembagus 168 teenagers. Using a scale addicted to online games, confidence and social interaction that will impact analysis to know. Hence analysis techniques the data used was pearson correlation.The result of the research is 200 >0,05 which means there is a confidence with social interaction in adolescents addicted to online games.